The betrothed / 1. - Cass, Kiera (The betrothed, 2020)
"When King Jameson declares his love for Lady Hollis Brite, Hollis is shocked--and thrilled. After all, she's grown up at Keresken Castle, vying for the king's attention alongside other daughters of the nobility. Capturing his heart is a dream come true. But Hollis soon realizes that falling in love with a king and being crowned queen may not be the happily ever after she thought it would be. And when she meets a commoner with the mysterious power to see right into her heart, she finds that the future she really wants is one that she never thought to imagine"--Provided by publisher.